Mengkaji Pemahaman Umat tentang Makna Ritual Huler Wair dalam Tradisi Upacara Pemberkatan Rumah Baru di Stasi Tilang Paroki Hati Tak Bernoda Sta. Perawan Maria Tilang Keuskupan Maumere - Veronika Yulita; Graciana Amanda Bele; Florens Maxi Un Bria (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
Huler Wair is a traditional cultural ritual that continues to be preserved by the Catholic community of Tilang Station, Immaculate Heart of the Blessed Virgin Mary Tilang Parish, Diocese of Maumere, particularly during the blessing ceremony of a new house. Passed down through generations, this ritual embodies significant religious, social, and cultural values within the local community. This study aims to analyze the community's understanding of the meaning of the Huler Wair ritual, identify the supporting and inhibiting factors affecting such understanding, and examine efforts to preserve the ritual as part of the house-blessing tradition. A qualitative research method with a descriptive approach was employed. Data were collected through structured interviews and documentation studies and analyzed using data collection, data reduction, data presentation, and conclusion drawing techniques. The findings reveal that the Huler Wair ritual is understood as an expression of prayer and hope for peace, safety, health, harmony, and well-being for the household members. Furthermore, the ritual symbolizes harmonious relationships among humans, God, fellow community members, and nature. The preservation of this tradition is supported by the active involvement of customary leaders, religious leaders, and community members. However, declining interest among younger generations and the growing influence of social media pose significant challenges to its continuity. Preservation efforts include involving young people in ritual activities, promoting awareness of its cultural values, and transmitting the tradition through customary and religious events to ensure that the Huler Wair ritual remains sustainable amid contemporary social change.